Effect of disorder on magnetic properties and martensitic transformation of Co-doped Ni-Mn-Al Heusler alloy. (November 2018) - Lyange, M.V.; Sokolovskiy, V.V.; Taskaev, S.V.; Karpenkov, D. Yu.; Bogach, A.V.; Zheleznyi, M.V.; Shchetinin, I.V.; Khovaylo, V.V.; Buchelnikov, V.D.
Abstract: Influence of Co addition on magnetic, transport properties and electron structure of Ni50− x Co x Mn31+ y Al19− y ( x = 0-10, y = 0-3) Heusler alloys were investigated experimentally and theoretically by first-principles calculations in the framework of density functional theory with an account of supercell approach. Cobalt doping from 0 to 10 at. % was found to increase the martensitic transition temperature T 0 = ( M s + A f )/2 from 280 to 365.5 K. Magnetization of austenite phase sharply increases and magnetic order changes from antiferromagnetic to ferromagnetic state, while in martensite phase magnetization slightly growing with cobalt content. From theoretical point of view, Co-doping leads to formation of additional exchange interactions between magnetic moments of Co-Mn and Ni-Co atoms, which leads to ferromagnetism in austenite. Theoretical calculations show that from 4.68 at. % of Co content ferromagnetic order is preferred. Martensitic transformation is suppressed in alloys with more than 9.5 at. % of cobalt. It was supported by theoretical calculations of the energy difference between austenite and martensite states as a function of cobalt content. We show that the energy difference between austenite and martensite phases in L21 structure from x ≥ 6.25 at. % of Co became negative, what points on the absence of martensitic transformation. For B2 structure, the energy difference is positive for all concentrations of cobalt, that proves that phase transition is likely to occur. Highlights: The martensitic transformation is suppressed by Co content higher than 9.5 at.%. An addition of Co results in an enhancement of ferromagnetism. Contrary, for the L21 ordered Ni-(Co)-Mn-Al, the martensitic phase becomes unstable.